The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/10934529.2015.1094351
|View full text |Cite
|
Sign up to set email alerts
|

Degradation ofsec-hexylbenzene and its metabolites by a biofilm-forming yeastTrichosporonasahiiB1 isolated from oil-contaminated sediments in Quangninh coastal zone, Vietnam

Abstract: This article reports on the ability of yeast Trichosporon asahii B1 biofilm-associated cells, compared with that of planktonic cells, to transform sec-hexylbenzene and its metabolites. This B1 strain was isolated from a petroleum-polluted sediment collected in the QuangNinh coastal zones in Vietnam, and it can transform the branched aromatic hydrocarbons into a type of forming biofilm (pellicle) more efficiency than that the planktonic forms can. In the biofilm cultivation, seven metabolites, including acetoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…According to previous reports, Trichosporon species have been isolated from a wide range of substrates, including human hair, soil, and cheese, which should be the sources of the accumulated Trichosporon in activated sludge (Cho et al 2015;Evans and Seviour 2012). Previous reports have indicated that Trichosporon hyphae are involved in the formation of biofilms and sludge flocs and contribute greatly to the degradation of caffeine and sec-hexylbenzene in wastewater (Lakshmi and Das 2013;Nhi-Cong le et al 2016). Cryptococcus species play important roles in wastewater treatment processes by converting large-molecule organics into small, degradable lipids (Santos et al 2014).…”
Section: Resultsmentioning
confidence: 95%
“…According to previous reports, Trichosporon species have been isolated from a wide range of substrates, including human hair, soil, and cheese, which should be the sources of the accumulated Trichosporon in activated sludge (Cho et al 2015;Evans and Seviour 2012). Previous reports have indicated that Trichosporon hyphae are involved in the formation of biofilms and sludge flocs and contribute greatly to the degradation of caffeine and sec-hexylbenzene in wastewater (Lakshmi and Das 2013;Nhi-Cong le et al 2016). Cryptococcus species play important roles in wastewater treatment processes by converting large-molecule organics into small, degradable lipids (Santos et al 2014).…”
Section: Resultsmentioning
confidence: 95%
“…Phenylalkanes are persistent organic pollutants which are mutagenic and carcinogenic. Nhi-Cong et al (2016) reported the biodegradation of sec-hexylbenzene by the yeast Trichosporon asahii B1, isolated from oil-contaminated sediments collected from the coastal area of Quangninh in Vietnam. This marine yeast transformed this branched side-chain benzene with biofilm-forming cells more efficiently than with planktonic cells.…”
Section: Petroleum Hydrocarbonsmentioning
confidence: 99%
“…The analysis was performed as described in our previous publication (Nhi-Cong et al, 2016). These experiments were conducted independently at least three times and calculated standard deviation (SD) values.…”
Section: Analysis Of Petroleum Hydrocarbon Degradation By High-perfor...mentioning
confidence: 99%